ESTIMATION OF CHARACTERISTIC PARAMETERS IN REGION-TIME-LENGTH ALGORITHM AND ITS APPLICATION - Rong D.-L.; Li Y.-R. (My University, 2007)
On the basis of gap's temporal-spatial characteristics in and around source area before an earthquake, we propose a method to estimate characteristic parameters (characteristic distance and time) in the region-time-length (RTL) algorithm and introduce the method of correlation coefficient developed by some authors in 2006 to determine the characteristic parameters. The anomalous seismic activities before four moderately strong earthquakes occurred in the northwestern and southwestern China in recent years are studied by the two methods. The results show that the method to estimate characteristic parameters advanced in this paper is a simple one, which possesses a physical meaning and is well applicable to the four moderately strong earthquakes studied. © 2007 Seismological Society of China.
Keywords: CHARACTERISTIC DISTANCE; CHARACTERISTIC TIME; RTL ALGORITHM